التسيير العمومي الجديد ودوره في تحقيق جودة الخدمة الصحية في الجزائر - دهان أحمد سعيد; عقاقبة عبد العزيز (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
تهدف هذه الدراسة إلى تناول موضوع التسيير العمومي الجديد باعتباره نموذجا تسييريًا مبتكرا للإدارة الحديثة ،بما يتضمنه من معايير مستلهمة من منظمات الأعمال ،والتي أثبتت فعاليتها في الواقع العملي و تم تكييفها مع متطلبات الإصلاح التي عرفها القطاع العام ، تزامنا مع تغير أدوار الدولة وتنافسية القطاع الخاص ،وعليه عرف القطاع الصحي في الجزائر إصلاحات مماثلة سعت في مجملها إلى رفع أداء المؤسسات الاستشفائية، بهدف تحقيق الكفاءة وتفعيل مشروع المؤسسة لتحقيق أفضل النتائج و تحسين الخدمات الصحية. This study aims to address the issue of the new public management as an innovative management model for modern management, including standards inspired by business organizations, which have proven effective in practice and have been adapted to the reform requirements known by the public sector, coinciding with the changing roles of the state and the competitiveness of the private sector. Accordingly, the health sector in Algeria knew similar reforms that sought in their entirety to raise the performance of hospital institutions, with the aim of achieving efficiency and activating the institution’s project to achieve the best results and improve health services.